Analysis of the shots in positions 1 and 2 in even situational framework during the World Championship of Barcelona 2013 - Sabio Lago, Y.; Cabedo Sanromà, J.; Guerra-Balic, M.; Argudo Iturriaga, F. M. (Journal of Human Sport & Exercise, 2020)
The purpose of this study was, on one hand, to know if the left-handed players were more effective in the goal categories and getting positive actions in 1 and 2 position than the right-handed in the same offense position in Even Situational Framework (FJa). On the other hand, to know if the shots in 1 and 2 position were less effective than the rest of the positions in the goal categories. The methodology was observational, multidimensional, nomothetic and punctual. The sample was all the throws of 24 games (12 male and 12 female) in the 2013 World Championship in Barcelona using an ad hoc instrument for observation through the SportCode software, which was also used to record the data. Descriptives and Chi-square test were obtained and the conclusions are that the left-handed players are more effective if we relate them to the goal categories and positive actions from positions 1 and 2. However, the righties are more effective if we only see the categories related with the goal.